Sulphonamide and trimethoprim resistance genes persist in sediments at Baltic Sea aquaculture farms but are not detected in the surrounding environment. - Windi Indra Muziasari; Satoshi Managaki; Katariina Pärnänen; Antti Karkman; Christina Lyra; Manu Tamminen; Satoru Suzuki; Marko Virta (PLoS ONE)
Persistence and dispersal of antibiotic resistance genes (ARGs) are important factors for assessing ARG risk in aquaculture environments. Here, we quantitatively detected ARGs for sulphonamides (sul1 and sul2) and trimethoprim (dfrA1) and an integrase gene for a class 1 integron (intI1) at aquaculture facilities in the northern Baltic Sea, Finland. The ARGs persisted in sediments below fish farms at very low antibiotic concentrations during the 6-year observation period from 2006 to 2012. Although the ARGs persisted in the farm sediments, they were less prevalent in the surrounding sediments. The copy numbers between the sul1 and intI1 genes were significantly correlated suggesting that class 1 integrons may play a role in the prevalence of sul1 in the farm sediments through horizontal gene transfer. In conclusion, the presence of ARGs may limit the effectiveness of antibiotics in treating fish illnesses, thereby causing a potential risk to the aquaculture industry. However, the restricted presence of ARGs at the farms is unlikely to cause serious effects in the northern Baltic Sea sediment environments around the farms.